Psychometric Evidence and Scoring Norms of the Psychopathic Personality Scale (R-22) in Peruvian Inmates - Trejo Calixto, Rogger German (2025)
The objective of this research was to evaluate the psychometric properties and establish scoring norms for the Psychopathic Personality Scale in a sample of Peruvian inmates. The study was divided into two stages: in the first stage, 273 inmates (aged between 21 and 75 years, with a mean age of 42.57 and a standard deviation of 10.59) were assessed through exploratory factor analysis. In the second stage, 871 volunteers (aged between 21 and 75 years, with a mean age of 40.77 and a standard deviation of 10.47) were evaluated. In the first study, the factor structure was described using exploratory factor analysis, yielding a total explained variance of 54.01%, which indicates an acceptable internal structure of the construct. In the second study, confirmatory factor analysis was used to obtain goodness-of-fit index values, reporting acceptable fit parameters (χ2/df = 3.891, CFI = .924, TLI = .910, SRMR = .057, RMSEA = .071). Reliability was assessed through internal consistency, obtaining ordinal α values ranging from .68 to .82 and ω values ranging from .59 to .79, all within an acceptable range. In conclusion, the psychometric properties of the Psychopathic Personality Scale (R-22) are supported in a sample of inmates.